Country-related future research agenda of Lean Manufacturing–A systematic literature review. Issue 4 (23rd July 2021) - Psomas, Evangelos
Abstract : Purpose: Many future research proposals of Lean Manufacturing (LM) are presented in the literature. The purpose of this paper is to determine these future research proposals of LM which are country-related and classify them. Design/methodology/approach: A systematic literature review (SLR) of peer-reviewed journal articles in LM was conducted. A total of 145 articles published in 34 journals during 2010–2020 were collected from four major management science publishers namely, Emerald Online, Elsevier/Science Direct, Springer Link and Taylor and Francis. The country-related future research proposals of LM identified in the literature were classified according to, firstly, the continent of the country of reference, and secondly, some form of natural affinity of these proposals creating meaningful themes. The quality tool "affinity diagram" was applied to classify the country-related future research proposals of LM. Findings: The country-related future research proposals of LM, which are increasing in the literature over time, refer mostly to studies to be conducted in several continents/countries and to multinational studies. Conducting studies specifically in Asia, Europe, South and North America, Africa and Australia–New Zealand is also suggested. The plethora of the country-related future research proposals of LM were classified, based on the affinity of their content, into 18 meaningful themes. These themes were also classified based on their affinity into two broad categories, namely "themes concerning the LM approach itself" and "themes concerning factors outside the LM approach". Research limitations/implications: The restricted number of the databases searched and the subjectivity of classifying the large number of the country-related future research proposals into themes are the main limitations of the present SLR. Based on these limitations, future literature review studies can be carried out. Practical implications: Useful proposals are provided to researchers of several countries for conducting original and country-specific research studies which can enrich the knowledge of the implementation of LM under the specific circumstances of a country for the benefit of practitioners. Originality/value: This study goes beyond previous literature review studies on LM by focusing exclusively on the LM future research agenda which is country related. The analytical presentation of the country-related future research proposals as well as the formulation of clusters of these proposals make the present SLR study substantially different from those carried out worldwide so far.